PENGARUH CITRA MEREK DAN KEPERCAYAAN TERHADAP MINAT BELI ULANG KOPI KAPAL API PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ABDURACHMAN SALEH SITUBONDO DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Feri, Feri; Karnadi, Karnadi; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The Influence of Brand Image and Trust in Repurchasing Interest of Kapal Api Coffee in Students of the Faculty of Economics and Business, Abdurachman Saleh University Situbondo With Customer Satisfaction as an Intervening Variable. Students of the Faculty of Economics and Business, Abdrachman Saleh Situbondo University, are the students with the largest quantity at Abdrachman Saleh Situbondo University. Students of the Faculty of Economics and Business, University of Abdrachman Saleh Situbondo are divided into three study programs. Marketing, HRM and finance Until now, the students of the Faculty of Economics and Business, Abdrachman Saleh University, Situbondo, have continued to grow. with Customer Satisfaction as an Intervening Variable. This research is an explanatory research. The population in this study were students of the Faculty of Economics and Business, University of Abdrachman Saleh Situbondo. The sampling technique was determined by quata sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that brand image has a significant effect on customer satisfaction, trust has a significant effect on customer satisfaction, brand image has a negative but not significant effect on repurchase intention Trust has a significant effect on repurchase intention, customer satisfaction has a significant effect on repurchase intention. The results of the indirect effect hypothesis test show that the brand image variable has a significant effect on repurchase intention through customer satisfaction, trust has a significant effect on repurchase intention through customer satisfaction.